LOWER EXTREMITIES MUSCLE CONTRIBUTIONS TO HORIZONTAL AND VERTICAL ACCELERATION OF THE CENTER OF MASS DURING THE FIRST STANCE PHASE IN SPRINTING OF SOCCER PLAYER (Vietnam Journal of Community Medicine, 2026)
Introduction: Sprinting is one of the most important activities in soccer that affects the outcome performance of players. The acceleration ability of the first stance phase was suggested to play a key role in sprinting performance of soccer players. The purpose of this study was to identify how lower limb muscles contributed to the acceleration of the center of mass (COM) and to determine primary muscles during the first stance phase of sprinting in soccer players to develop training program in minimizing injury risk or in strengthening key muscle groups enhancing the effectiveness of rehabilitation for athletes before return to competition.Methods: Five female soccer players sprinted for 5 meters, at a Laboratory room. Vicon system and force plates were used to collect maker trajectories and ground reaction forces. The contribution of each muscle was calculated by an analysis tool in Opensim. Results: Gastrocnemius and soleus muscles contributed the highest (24.6% and 25.3%, respectively) to the total forward acceleration of the whole body. Similarly, approximately 37% of the total upward acceleration of the COM was induced by the soleus, while 36.1% was induced by the gastrocnemius. Hip extensors induced nearly 22.2% of the total forward acceleration, while the quadriceps contributed around 10% of the total upward acceleration.Conclusion: Gastrocnemius and Soleus play key roles in acceleration performance, and this muscle group should be highly focused on training and treatment for sprinting motion of soccer players. Similarly, Hamstrings and gluteus muscles are also considered to enhance acceleration performance.